Better Together - Riccio, Christine, 1990- (New York : Wednesday Books, 2021)
Jamie's an aspiring stand-up comic in Los Angeles with a growing case of stage anxiety. Siri's a stunning ballering from New Jersey dealing with a career-changing injury. When the two girls meet at the Rediscover Yourself retreat in Colorado, they discover they are sisters separated as young children by their bitterly divorced parents.
Kirkus Review - Adult,051521
School Library Journal
7-12.
Keywords: Sisters -- Fiction; Adult children of divorced parents -- Fiction; Health resorts -- Colorado -- Fiction; Colorado -- Fiction; Domestic fiction